(untitled) (Biological Sciences - PJSIR, 2015)
Antibacterial activity of aqueous extract of Terminalia catappa, Momordica charantia and Acalypha wilkesiana was investigated against Escherichia coli isolated from pediatrics with the minimum inhibitory concentration (MIC) of 0.5mg/mL by agar dilution technique. The antibacterial potency of the extracts as evaluated by broth dilution technique, showed diameter of inhibition zone of 22.80 mm, 14.20 mm and 21.00 mm at a concentration of 0.5 mg/mL for T. catappa, M. charantia and A. wilkesiana, respectively. The antibacterial effect of T. catappa was found to be more pronounced with its plausible use for the treatment of infections caused by E. coli.